(untitled) (London Journal of Medical and Health Research, 2025)
Homo Sapiens is the most dangerous species ever to live on earth. Compared to other animals, its communications skills are inferior being dependant on speaking but can record language which helps it to make tools most of which are weapons. These skills could be diverted to peaceful purposes. This article describes the behaviour of the species and shows how it can save itself from self-inflicted extinction.